2016
DOI: 10.15580/gjpbcs.2016.3.040916076
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Gain in Grain and Oil Yields, Oil Content and Associated Traits of Linseed (Linum usitatissimum L.) in Ethiopia

Abstract: ABSTRACT. These significant and linear genetic gains showed that there is no indication of a yield plateau for linseed breeding in Ethiopia. Therefore, the effort should be strengthened and continued to achieve more progresses in these and other relevant traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This clearly indicates that chickpea breeders have made efforts over the last 35 years to improve the yield of Kabuli type chickpea in Ethiopia, but this increase was not significantly different from zero (Table 7), rather they get substantial improvement in hundred seed weight. Likewise, Ersullo [24] noticed that an average rate of increase in grain yield potential per year of release since pre-1984 was non-significant (4.329 kg ha -1 yr -1 ) when tested under the four locations for linseed. Similarly, Koemel [30] indicated the more recent entries failed to improve grain yield of hard winter wheat over that of the long-term check cultivars.…”
Section: Grain Yield Potentialmentioning
confidence: 95%
See 3 more Smart Citations
“…This clearly indicates that chickpea breeders have made efforts over the last 35 years to improve the yield of Kabuli type chickpea in Ethiopia, but this increase was not significantly different from zero (Table 7), rather they get substantial improvement in hundred seed weight. Likewise, Ersullo [24] noticed that an average rate of increase in grain yield potential per year of release since pre-1984 was non-significant (4.329 kg ha -1 yr -1 ) when tested under the four locations for linseed. Similarly, Koemel [30] indicated the more recent entries failed to improve grain yield of hard winter wheat over that of the long-term check cultivars.…”
Section: Grain Yield Potentialmentioning
confidence: 95%
“…Generally speaking, better genetic improvement was obtained from breeding for hundred seed weight than it was from breeding for grain yield as far as Kabuli type chickpea is concerned. Likewise, Amsal [18] in durum wheat, Ortiz [32] in tworow Nordic spring barley, Tamene [21] in faba bean and Ersullo [24] in linseed found that thousand seed weight of modern varieties were heavier than the older ones. Contrary to the present study, [19] in tef, [20] in haricot bean, [22] in food barely noticed non-significant change in seed weight.…”
Section: Grain Yield Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent method, the GGE (genotype main effect (G) plus G x E interaction) biplot model, provides breeders a more complete and visual evaluation of all aspects of the data by creating a biplot that simultaneously represents mean performance and stability, as well as identifying mega-environments [1,11,13]. Previous works that has been reported on linseed genotypes performance stability in Ethiopia were limited and either based on multivariate statistics such as AMMI or have been used only few regression/parametric and non-parametric approaches [6,14,15,16,17]. In this experiment, we attempted to apply AMMI and sites regression GGE biplot statistical model for determination of the magnitude and pattern of G × E interaction effects and performance stability of oil yield in linseed genotypes.…”
Section: Introductionmentioning
confidence: 99%